Attitudes towards offenders with mental health problems scale. Issue 2 (11th May 2015) - Glendinning, Anna Louise; O'Keeffe, Ciaran
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to suggest that there was a need for a psychometric measure to assess attitudes specifically towards offenders with mental health problems. The "Community Attitudes towards the Mentally Ill" scale (CAMI; Taylor and Dear, 1981) was adapted to create a new psychometric measure; the "Police and Community Attitudes towards Offenders with Mental Illness" scale (PACAMI-O). Design/methodology/approach – A sample of police and community participants (n=178) completed this scale through the online surveying system, Psychdata. The new psychometric measure utilised the same 40 items featured in the CAMI; although, the wording was adapted. Findings – The internal reliability for the combined sample was high (α=0.929), which implied very good internal reliability. An exploratory factor analysis identified four new factors: Self-Preservation, Societal Reservation, Mental Health Awareness and Treatment Ideology. A t-test revealed there was a significant difference between the scores of the police and community sample, with the effect size depicting a large magnitude between the means (t(176)=p=0.019, η2=0.16). Practical implications – The PACAMI-O scale appears adequate for measuring attitudes towards its targeted sample and has shown utility with; a professional group (police officers and custody sergeants) who potentially face such offenders (primarily in the context of using Section 136 of the Mental Health Act). It therefore has practical implications in assessing attitudes with other groups within forensic mental health. Originality/value – Assessing attitudes towards offenders with mental health problems would enable a better understanding of the formation of negative attitudes and stigmatisation and therefore, ways of tackling treatment, rehabilitation and also community reintegration.